Growth and yield performance of maize at red-yellow podzolic acid soil after oil palm empty fruit bunches compost and rice husk charcoal application - M Mardhiana; Dwi Apriyani; Muh Adiwena; Ankardiansyah Pandu Pradana (Brawijaya University, 2021)
On acid soils, maize growth cannot be optimal because of the high content of Al, Fe, Mg, and Zn, which has the potential to poison plants. Several nutrients such as P, Cu, and S are also available in small quantities for plants, thus inhibiting growth. This study aimed to determine the effectiveness of oil palm empty fruit bunches compost and rice husk charcoal in increasing the growth and yield of maize on red-yellow podzolic acid soils. Bonanza F1 varieties were planted and treated with (T1) 5 t ha-1 of oil palm empty fruit bunches compost; (T2) 10 t ha-1 of oil palm empty fruit bunches compost; (T3) 5 t ha-1 rice husk charcoal; (T4) 10 t ha-1 rice husk charcoal; and (T5) 5 t ha-1 of oil palm empty fruit bunches compost + 5 t ha-1 of rice husk charcoal, and control plants were not given any treatment. The results showed that all treatments had a better and significantly different effect than the control plants. The application of oil palm empty fruit bunches compost and rice husk charcoal could boost plants height (149.75% - 289.88%), stems diameter (124.10% - 204.62%), number of leaves (131.01% - 223.26%), plants fresh weight (204.14% - 342.25 %), plants dry weight (136.77% - 165.76%), weight of maize cobs (178.77% - 292.72%), weight of maize cobs without maize husks (158.27% - 233.03%), maize cobs length (112.44% - 147.14%), maize cobs diameter (117.16% - 187.79%), and the weight of 100 maize kernels (110.92% - 201.72%). Among all treatments, the T5 treatment (5 t ha-1 of oil palm empty fruit bunches compost + 5 t ha-1 rice husk charcoal) was the best because it consistently gave the highest yields on all observed variables.